2016
DOI: 10.1002/ejoc.201600026
|View full text |Cite
|
Sign up to set email alerts
|

GAP Peptide Synthesis through the Design of a GAP Protecting Group: An Fmoc/tBu Synthesis of Thymopentin Free from Polymers, Chromatography and Recrystallization

Abstract: A novel method for Fmoc/tBu solution-phase peptide synthesis and the development of a new benzyl-type GAP protecting group is reported. This new GAP protecting group is utilized in place of a polymer support, facilitating C→N Fmoc peptide synthesis without chromatography, recrystallization, or polymer supports. The GAP group can be added and removed in high yield, and was used to synthesize over 1 gram of the immunostimulant, thymopentin, in high overall yield (83%) and purity (99%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…This chirality belongs to a type of Multilayer Organic Framework (M-LOF) of single organic molecules with pseudo C 2 -chiral characteristics. The key element of this chirality is characterized by three layers of planes that are arranged nearly in parallel fashion with one on top and one below the planar center as presented in Figure 1 This discovery was resulted from our Group-Assisted Purification (GAP) chemistry by taking advantage of Nphosphonyl imine reagents and their usage for asymmetric reactions (Figure 2(a), a-c) [41][42][43][44][45][46][47]. In this project, we found that chiral and achiral N-phosphonyl-or N-phosphinyl groups avoided the formation of oily and sticky products; instead, they afforded special crystalline solids that can be purified simply by washing crude products with common petroleum solvents without the use of column chromatography and recrystallization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This chirality belongs to a type of Multilayer Organic Framework (M-LOF) of single organic molecules with pseudo C 2 -chiral characteristics. The key element of this chirality is characterized by three layers of planes that are arranged nearly in parallel fashion with one on top and one below the planar center as presented in Figure 1 This discovery was resulted from our Group-Assisted Purification (GAP) chemistry by taking advantage of Nphosphonyl imine reagents and their usage for asymmetric reactions (Figure 2(a), a-c) [41][42][43][44][45][46][47]. In this project, we found that chiral and achiral N-phosphonyl-or N-phosphinyl groups avoided the formation of oily and sticky products; instead, they afforded special crystalline solids that can be purified simply by washing crude products with common petroleum solvents without the use of column chromatography and recrystallization.…”
Section: Introductionmentioning
confidence: 99%
“…In this project, we found that chiral and achiral N-phosphonyl-or N-phosphinyl groups avoided the formation of oily and sticky products; instead, they afforded special crystalline solids that can be purified simply by washing crude products with common petroleum solvents without the use of column chromatography and recrystallization. We also found these GAP groups can increase chemical yields [46], particularly for peptide synthesis, which is defined as Group-Assisted Synthesis (GASyn) [47]. GASyn chemistry has resulted in nearly quantitative yield for each step of polypeptide synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Its synthesis began with the benzylic and phosphine oxidation of commercially available, diphenyl( p -tolyl)phosphine 1 with potassium permanganate to benzoic acid 2 . ( Scheme 1 ) Esterification followed by reduction with borohydride gave the first GAP-anchored benzyl alcohol 4 , or “dppBnOH,” in high yield (Seifert et al, 2016 ). Similarly, the condensation of diphenylphosphane 5 with 4-chlorobenzonitrile 6 , provided 4-(diphenylphosphanyl)benzonitrile 7 , which upon reduction with LiAlH 4 resulted in amine 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group has established a concept called GAP chemistry for greener synthesis where functionalities of special interest are incorporated into the substrates to facilitate the purification of crude products based on solubility without column chromatography or recrystallization. The pure products can be readily obtained simply by washing the crude mixture with common solvents or cosolvents (Wang et al, 2013 ; Chennapuram et al, 2014 ; Dommaraju and Prajapati, 2015 ; Seifert et al, 2016 ; Patel et al, 2019 ). Indeed, GAP chemistry would be the first concept consisting of both chemical aspects (reagent and reaction) and physical aspects (separation and purification).…”
Section: Introductionmentioning
confidence: 99%
“…Seifert et al developed a soluble and re-usable diphenylphosphine oxidebenzyl tag (HOBndpp, Fig. 10A) for LPPS of a pentamer in excellent yield and purity without chromatography, 113 tri(4-benzoylphenyl) phosphate (TBP), 115 and diphenylphosphinyloxyl diphenyl ketone (DDK) 116 scaffolds (Fig. 10A), enabling Boc and Fmoc LPPS of up to 16-mer peptides in good yields without intermediate HPLC purication.…”
Section: Liquid-phase and Membrane-enhanced Peptide Synthesismentioning
confidence: 99%